Light in a Dark Place : The Doctrine of Scripture. - Feinberg, John S. (Crossway, 2018)
What we believe about the Bible is foundational to every part of life. Scripture is the very Word of God, the final authority for all of theology, the governing source of all other doctrines. In the latest volume of the Foundations of Evangelical Theology series, theology professor John S. Feinberg has written a landmark work on the doctrine of Scripture, offering a robust, serious treatment of topics such as revelation, the canon, inerrancy, infallibility, sufficiency, preservation, and more―all with the goal of helping readers cherish, obey, and be transformed by what God has spoken in his Word.